THE EFFECTS OF INFORMATION PRODUCTION PROCESS ON EXPERIENCE AND EVALUATION - Rusho, Yonit; Raban, Daphne R. (AoIR Selected Papers of Internet Research, 2018)
Research to date on the value of information has mostly focused on the consumption side of information, namely, that consumers need to experience information in order to evaluate it. When it comes to digital media, users have multiple roles. In this context, materiality is applied to assess the role that technological components play in the interaction between user and digital media. The concurrent consumption and production of information raises questions as to the influence of information production on information value perception. To this end, we conceptualize the information production process. The fundamental assumption in this research is that value perception changes as a result of production experience. Furthermore, this study examines the boundaries of value perception for producers of information. 309 participants took part in a set of experiments. Willingness-to-pay by consumers and willingness-to-accept payment by producers were measured before and after consumption/ production/ peer-production. Results show that consumers’ and producers’ subjective value before their experience were equivalent; Change in value perception before and after consumption/production produced a statistically significant effect; Producers who evaluate the information after the experience, evaluated it higher than producers who evaluated the information before the experience; and value perception measured before the production by a single producer is lower than value perception by peer-producers. Hypotheses were accepted. If accepted, additional results will be presented at the conference.